Strategi Pengembangan Usaha pada UMKM Depot Kusen Rahmat dengan Menggunakan Teknik Analisis SWOT dan QSPM - Ayu Ardiyanti; Neneng Miskiyah; Hendra Sastrawinata (Jurnal Manajemen Bisnis Era Digital, 2025)
This study aims to analyze the business development strategy of Depot Kusen Rahmat by reviewing four main aspects, namely production, human resources (HR), finance, and marketing. The analytical approach used in this study is SWOT (Strengths, Weaknesses, Opportunities, Threats) and QSPM (Quantitative Strategic Planning Matrix). Primary data was obtained through a survey of 16 respondents who are active consumers of Depot Kusen Rahmat. The results of the SWOT analysis identified that the company has four strengths, four weaknesses, four opportunities, and four threats. The most dominant internal strength is efficient and neat products, with the highest weighted score of 0.509, which indicates that the quality of production results is the main competitive advantage. On the other hand, the main weakness found is the absence of a product catalog, with a score of 0.158, which indicates a lack of visual information media as a means of product promotion and communication to consumers. From external factors, the biggest opportunity is the increasing consumer interest in custom products, with a score of 0.479, which indicates a positive trend towards product personalization. The most significant threat is the rapidly changing design trends, with a score of 0.186, which requires the company to be more adaptive to changing market tastes. Based on the results of the SWOT matrix analysis, the company's position is in Quadrant I with an IFAS value of 1.368 and EFAS of 1.206, which indicates that the company is in a position to support an aggressive growth strategy. The QSPM results recommend prioritizing strategies in the form of emphasizing quality and balanced prices, followed by improving customer service and developing high-quality custom products as strategic steps to win market competition and increase business competitiveness sustainably.